Measuring technical variability in illumina DNA methylation microarrays. - Anderson A Butler; Jason J Kras; Karolina P Chwalek; Enrique I Ramos; Isaac J Bishof; David S Vogel; Daniel L Vera (PLoS ONE)
DNA methylation microarrays have become a widely used tool for investigating epigenetic modifications in various aspects of biomedical research. However, technical variability in methylation data poses challenges for downstream applications such as predictive modeling of health and disease. In this study, we measure the impact of common sources of technical variability in Illumina DNA methylation microarray data, with a specific focus on positional biases inherent within the microarray technology. By utilizing a dataset comprised of multiple, highly similar technical replicates, we identified a chamber number bias, with different chambers of the microarray exhibiting systematic differences in fluorescence intensities (FI) and their derived methylation beta values, which are only partially corrected for by existing preprocessing methods and demonstrate that this positional bias can lead to false positive results during differential methylation testing. Additionally, our investigation identified outliers in low-level fluorescence data which might play a role in contributing to predictive error in computational models of health-relevant traits such as age.